Dependence of the bystander effect for micronucleus formation on dose of heavy-ion radiation in normal human fibroblasts. Issue 1 (4th August 2015) - Matsumoto, Yoshitaka; Hamada, Nobuyuki; Aoki-Nakano, Mizuho; Funayama, Tomoo; Sakashita, Tetsuya; Wada, Seiichi; Kakizaki, Takehiko; Kobayashi, Yasuhiko; Furusawa, Yoshiya
Abstract : Ionising radiation-induced bystander effects are well recognised, but its dependence on dose or linear energy transfer (LET) is still a matter of debate. To test this, 49 sites in confluent cultures of AG01522D normal human fibroblasts were targeted with microbeams of carbon (103 keV µm −1 ), neon (375 keV µm −1 ) and argon ions (1260 keV µm −1 ) and evaluated for the bystander-induced formation of micronucleus that is a kind of a chromosome aberration. Targeted exposure to neon and argon ions significantly increased the micronucleus frequency in bystander cells to the similar extent irrespective of the particle numbers per site of 1–6. In contrast, the bystander micronucleus frequency increased with increasing the number of carbon-ion particles in a range between 1 and 3 particles per site and was similar in a range between 3 and 8 particles per site. These results suggest that the bystander effect of heavy ions for micronucleus formation depends on dose.